Is food desirability affected by social interaction?. (June 2016) - Rizzato, Matteo; Di Dio, Cinzia; Fasano, Fabrizio; Gilli, Gabriella; Marchetti, Antonella; Sensidoni, Alessandro
Highlights: This study investigates the effect of an emotional context on food desirability. Happiness, anger and a neutral facial expression denoted the emotional context. Happiness exerted a positive effect comparable to a no-(emotional) context condition. Anger, selected as a food-unrelated emotion, showed a negative effect on desirability. Also the neutral expression evoked negative influential effects on desirability. Abstract: The experience of food can be affected by visual perception and the context in which food is presented. In this study, we investigated the effect of specific emotional contexts on food desirability. To this purpose, we selected a highly familiar Italian food, Pizza Margherita, whose sauce color was digitally manipulated to create different desirability levels. The participants rated the pizza desirability on the basis of its visual features alone (no-context condition) and, most critically, after viewing images representing facial expressions of happiness, anger and neutrality. Anger was selected, as opposed to disgust, as a food-unrelated emotion to assess whether influential effects on food desirability evoked by the observed individual's emotion state needs to be necessarily related to the eating context. Confirming previous results, we found an effect of the social context (facial expressions) on food desirability. Similarly to the no-context condition, happiness evoked the highest desirability ratings for all items compared to neutral and angry expressions, whereas the neutral and angry faces negatively affected food desirability relative to no-context and happy face conditions. These findings show that happiness is commensurate with a situation in which food is presented alone, suggesting that approach to food in healthy individuals is intrinsically related to positive emotions. Additionally, we show that food perception can be also affected by emotions, which are not necessarily related to food, but which nevertheless frame food delivery. We argue that this emotion-related effect may be grounded on resonance 'mirror' mechanisms allowing people to spontaneously tune to others' emotions.